In Cognitive Radio Network Multiple Relay Hybrid Approach Used for Improving Security and Reliability Trade Off: Performance analysis of Hybrid Cognitive Relay Network for Improving Security and Reliability Trade Off (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In radio spectrum the problem of underutilization has been solved by cognitive radio. The cognitive radio devices intelligently sense and feat the part of spectrum. Hybrid Cognitive Radio Network approach is useful to improving the security and reliability of the network. Hybrid cognitive radio network jointly used both the cognitive and licensed radio networks. This paper analyses the performance of Hybrid Cognitive relay network for single relay and multiple relay under AWGN and rician fading channels. The performance metrics such as channel capacity, bit error rate and outage probability are formulated and numerical simulations by using MATLAB are performed. This analysis is helpful in determining the Capacity and Bit error rate for optimum usage of power and bandwidth is better. This analysis is also helpful to compare the result of single relay and multiple relay hybrid graphs.